Reversal of charge selectivity in transmembrane protein pores by using noncovalent molecular adapters. - Gu, L; Dalla Serra, M; Vincent, J; Vigh, G; Cheley, S; Braha, O; Bayley, H (2000)
In this study, the charge selectivity of staphylococcal alpha-hemolysin (alphaHL), a bacterial pore-forming toxin, is manipulated by using cyclodextrins as noncovalent molecular adapters. Anion-selective versions of alphaHL, including the wild-type pore and various mutants, become more anion selective when beta-cyclodextrin (betaCD) is lodged within the channel lumen. By contrast, the negatively charged adapter, hepta-6-sulfato-beta-cyclodextrin (s(7)betaCD), produces cation selectivity. The cyclodextrin adapters have similar effects when placed in cation-selective mutant alphaHL pores. Most probably, hydrated Cl(-) ions partition into the central cavity of betaCD more readily than K(+) ions, whereas s(7)betaCD introduces a charged ring near the midpoint of the channel lumen and confers cation selectivity through electrostatic interactions. The molecular adapters generate permeability ratios (P(K+)/P(Cl-)) over a 200-fold range and should be useful in the de novo design of membrane channels both for basic studies of ion permeation and for applications in biotechnology.